2018
DOI: 10.1371/journal.pone.0206082
|View full text |Cite
|
Sign up to set email alerts
|

Habitat preference and den characterization of Indian Pangolin (Manis crassicaudata) in a tropical lowland forested landscape of southwest Sri Lanka

Abstract: The Indian pangolin (Manis crassicaudata) is under threat due to hunting for local consumption and illegal trafficking of scales and meat. The dearth of scientific studies on the ecology of the M. crassicaudata has impaired accurate assessments of its conservation needs. This study investigated the habitat preference and burrow characteristics of M. crassicaudata in a tropical lowland rainforest in southwest Sri Lanka. A total of 75 burrows (54 feeding burrows and 21 resting burrows) of M. crassicaudata in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 13 publications
3
44
0
1
Order By: Relevance
“…However, the current legal framework for biodiversity conservation allowing the export of specimens outside Sri Lanka is very restrictive and might represent a serious limitation to the completion of the taxonomic work that could be undertaken within the country. Moreover, with ongoing landscape modification in the region, many species have been driven to critical status ( Somaweera et al 2015 ; Perera et al 2017 ; Karawita et al 2018 ), therefore, urgent, large-scale, and sustained efforts to monitor, characterize, and conserve the ant fauna of Sri Lanka is critical.…”
Section: Resultsmentioning
confidence: 99%
“…However, the current legal framework for biodiversity conservation allowing the export of specimens outside Sri Lanka is very restrictive and might represent a serious limitation to the completion of the taxonomic work that could be undertaken within the country. Moreover, with ongoing landscape modification in the region, many species have been driven to critical status ( Somaweera et al 2015 ; Perera et al 2017 ; Karawita et al 2018 ), therefore, urgent, large-scale, and sustained efforts to monitor, characterize, and conserve the ant fauna of Sri Lanka is critical.…”
Section: Resultsmentioning
confidence: 99%
“…The behavioral plasticity of the Indian pangolin has enabled it to inhabit an array of natural and human-modified landscapes [ 1 ]. It has been reported that Indian pangolins exhibit different behavioral adaptations in lowland wet zone habitats and dry zone habitats in Sri Lanka [ 7 ]. The specific habitat an individual occupies can further affect the wearing of the claws and scales [ 7 , 8 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hunting, poaching, and trafficking, primarily driven by the demand for its keratinous scales and meat, have made the Indian pangolin threatened across its range [ 2 ]. Despite being identified as “endangered” globally and nationally, limited studies have been conducted on Indian pangolins found in Sri Lanka [ 5 , 7 , 8 ], and the lack of scientific information on the species is a major impediment in the conservation of Indian pangolins [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus indirect methods such as camera trap surveys, sign surveys and community surveys are often used by researchers [[3], [4], [5]]. Field data gathered by the authors during ecological surveys to determine the abundance [6,7], and habitat utilization of Indian pangolins [5] in the South-west lowland forest and associated landscapes in Sri Lanka (Yagirala: 6°21′ to 6°26′ N and 80°08′ to 80°11′ E), and two other study locations (Wilpattu: °13′ to 8°40′N and 79°50′ to 80°10′E and Yala: 6°18′ to 6°42′N and 81°24–81°43′E) from August 2013 to December 2018 were used as primary data on pangolin recordings. We collected data on the distribution, rescue and wildlife crimes involving Indian pangolins from January 2000 to December 2018 to update the distribution and conservation status of Manis crassicaudata in Sri Lanka.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%